Android-Based Private Course Application - Lukman Harun Iskandar; Arif Senja Fitrani (Universitas Muhammadiyah Sidoarjo, 2021)
At this time technology has developed rapidly, without exception in the field of education. One of the technological developments in education is tutoring. Many students still need tutoring or private lessons to improve their abilities and meet the set passing grade standards. In addition, the catching power of each child in receiving subject matter at school is different so that not all are able to understand the material using offline or online methods. The purpose of this application is to make it easier and help the difficulties experienced by students and teachers to connect with each other and carry out private lessons. This application uses the method of observation and literature study. The method of making this application is the SDLC (System Development Life Cycle) prototype model. The expected results from making this application are so that teachers and students can connect with each other and carry out course activities easily according to the criteria desired by both parties. From this application students can choose based on the level of education and subjects they want to take and the rates offered by the teacher. Students and teachers can also choose the place of learning they want, such as studying at home, on video cameras or at the teacher's place.